2009
DOI: 10.1007/s10800-009-9801-x
|View full text |Cite
|
Sign up to set email alerts
|

ZnNi alloy electrodeposition from acid baths containing sorbitol or glycerol and characterization of ZnNi deposits

Abstract: The influence of sorbitol or glycerol on the electrodeposition of ZnNi alloys and on the morphology, composition and structure of the ZnNi deposits was investigated. The highest current efficiency (CE), around 90%, was obtained in the presence of glycerol in the potential range from approximately −1.30 V to −1.40 V, while in the presence of sorbitol or absence of either polyalcohol the CE was 82-85%, for the same potential range. Scanning electron microscopy (SEM) analysis showed that ZnNi deposition at −1.26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(66 reference statements)
3
13
0
Order By: Relevance
“…The Ni content in the ZnNi deposits produced in the presence of mannitol was raised from 6 to 10 wt% in the potential range -1.26 to -1.40 V. It was suggested that the ZnNi deposits obtained in these baths probably offered sacrificial protection to the substrate (steel). Also, these results corroborated those for ZnNi electrodeposition in the presence and absence of glycerol or sorbitol [17].…”
Section: Introductionsupporting
confidence: 84%
“…The Ni content in the ZnNi deposits produced in the presence of mannitol was raised from 6 to 10 wt% in the potential range -1.26 to -1.40 V. It was suggested that the ZnNi deposits obtained in these baths probably offered sacrificial protection to the substrate (steel). Also, these results corroborated those for ZnNi electrodeposition in the presence and absence of glycerol or sorbitol [17].…”
Section: Introductionsupporting
confidence: 84%
“…1 shows that the initial deposition potential (E d,I ), -1.15 V, did not change in any of the baths studied, implying that no complex was formed between zinc or nickel ions and the boric-mannitol anion. This result corroborates those previously obtained in our laboratory [14][15][16]. Figure 2 shows the voltammetric dissolution charge density (q diss ) of ZnNi deposits produced in baths without and with various amounts of mannitol (Table 1), in the same deposition time (40 s), plotted against deposition potential (E d ).…”
Section: Resultssupporting
confidence: 90%
“…Thus, the boric-mannitol complex works as a grain refiner and smoother. Also, these results corroborate those for ZnNi electrodeposition in the presence and absence of sorbitol, reported in an earlier study [14].…”
Section: Morphological Analysis Of Znni Depositssupporting
confidence: 92%
See 2 more Smart Citations